I want to find the asymptote oblique of the following function for $x\rightarrow\pm\infty$


For $x\rightarrow+\infty$ we have:


which means that the function grows linearly.

$$f(x)-mx=\sqrt{x^2+3x}-x=x\left(\sqrt{\frac{x^2}{x^2}+\frac{3x}{x^2}}-1\right)\sim x\left(\frac {1}{2}\cdot\frac{3}{x}\right)=\frac{3}{2}$$

The oblique asymptote is $y=x+\frac 3 2$ which is correct. For $x\rightarrow-\infty$ we have:


This means that

$$f(x)-mx=\sqrt{x^2+3x}+x=x\left(\sqrt{\frac{x^2}{x^2}+\frac{3x}{x^2}}+1\right)=x\left(\sqrt{1+\frac{3}{x}}+1\right)\sim x\cdot2\rightarrow -\infty$$

Which is not what my textbook reports ($-\frac{3}{2}$). Any hints on what I did wrong to find the $q$ for $x\rightarrow-\infty$?

  • $\begingroup$ If $x < 0$ (or, better, $x\leq -3$), one has $\sqrt{x^2+3x} = |x| \sqrt{1+3/x} = -x \sqrt{1+3/x}$. $\endgroup$ – Rigel Aug 18 '18 at 9:17
  • $\begingroup$ For the second write $\sqrt{x^2+3x}+x=\dfrac{3x}{\sqrt{x^2+3x}-x}\to-\dfrac32$. $\endgroup$ – Nosrati Aug 18 '18 at 9:31

The problem is in $$ f(x)-mx=\sqrt{x^2+3x}+x\underset{\begin{array}{c} \uparrow \\ \text{problem}\end{array}}{=}x\left(\sqrt{\frac{x^2}{x^2}+\frac{3x}{x^2}}+1\right)=x\left(\sqrt{1+\frac{3}{x}}+1\right)\sim x\cdot2\rightarrow -\infty $$ which should be $$ f(x)-mx=\sqrt{x^2+3x}+x=x\left(-\sqrt{\frac{x^2}{x^2}+\frac{3x}{x^2}}+1\right) $$ because we are near $-\infty$, so $\sqrt{x^2}=-x$.

In order to avoid such common mistakes, I suggest to change $x=-t$, when the limit for $x\to-\infty$ is involved: $$ \lim_{x\to-\infty}\bigl(\sqrt{x^2+3x}+x\bigr)= \lim_{t\to\infty}\bigl(\sqrt{t^2-3t}-t\bigr)= \lim_{t\to\infty}\frac{-3t}{\sqrt{t^2-3t}+t} $$ From here it should be clear.

Another strategy, in this case, is to set $x=-1/t$, that transforms the limit into $$ \lim_{t\to0^+}\left(\sqrt{\frac{1}{t^2}-\frac{3}{t}}-\frac{1}{t}\right)= \lim_{t\to0^+}\frac{\sqrt{1-3t}-1}{t} $$ which is a simple derivative: if $f(t)=\sqrt{1-3t}$, then $f'(t)=\frac{-3}{2\sqrt{1-3t}}$ and $$ \lim_{t\to0^+}\frac{\sqrt{1-3t}-1}{t}=f'(0)=-\frac{3}{2} $$


This is not a different way, but is better I think $$f(x)=\sqrt{x^2+3x}=\sqrt{x^2+3x+(\frac32)^2-(\frac32)^2}=\sqrt{\left(x+\frac{3}{2}\right)^2-(\frac32)^2}\sim\left|x+\frac{3}{2}\right|$$ which gives both oblique asymptotes.


$$f(x)=\sqrt{x^2+3x}=|x|\left(1+{3\over x}\right)^{1\over2}$$ which, as $x\rightarrow -\infty$, is equal to $$-x\left(1-{3\over{2x}}\right)^{1\over2} \sim -x\left(1+{3\over{2x}}\right)= -x -{3\over2}$$ using Taylor or Bernoulli

  • $\begingroup$ Thanks. I haven't studied Taylor nor Bernoulli yet. $\endgroup$ – Cesare Aug 18 '18 at 9:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.